2005
DOI: 10.1029/2005eo290002
|View full text |Cite
|
Sign up to set email alerts
|

Cross validating ocean prediction and monitoring systems

Abstract: With the ongoing development of ocean circulation models and real‐time observing systems, routine estimation of the synoptic state of the ocean is becoming feasible for practical and scientific purposes. The models can assist in ocean monitoring and regional dynamics studies, but only after they have been validated. For the first time, beginning 1 November 2004, independent ocean model estimates of the Florida Current (FC) volume transport are available, in real time, for cross validation with observed transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…In the Wind experiment, the Yucatan outflow Q y increases to 9.2 Sv and the inflow Q also increases to 33.2 Sv. We will shortly explain why; for now, Sheinbaum et al's (2002) observations (see also Candela et al 2002;Hamilton et al 2005) but are lower than those reported by and Mooers et al (2005). To estimate Q eddy , we first define the edge of an eddy as the SSH 5 0.1 m. The depth of the eddy is then set to 78C isotherm, which closely coincides with speeds under the core of the eddy of about 0.05 m s 21 .…”
Section: Eddy-propagation Tracks and Mass Balance In The Gulfmentioning
confidence: 85%
“…In the Wind experiment, the Yucatan outflow Q y increases to 9.2 Sv and the inflow Q also increases to 33.2 Sv. We will shortly explain why; for now, Sheinbaum et al's (2002) observations (see also Candela et al 2002;Hamilton et al 2005) but are lower than those reported by and Mooers et al (2005). To estimate Q eddy , we first define the edge of an eddy as the SSH 5 0.1 m. The depth of the eddy is then set to 78C isotherm, which closely coincides with speeds under the core of the eddy of about 0.05 m s 21 .…”
Section: Eddy-propagation Tracks and Mass Balance In The Gulfmentioning
confidence: 85%
“…The Florida Current itself varies over fairly short time scales, at times as much as 10 Sv over as short a period as 3 days (e.g., Mooers et al 2005). This will be a larger issue for the LADCP sections than for the dropsonde sections for the simple reason that the LADCP sections take roughly twice as long to occupy (12-14 vs 6 h).…”
Section: Transport Accuracymentioning
confidence: 99%
“…3.19): three anomalously low (outside of 2-3 standard deviations of the daily averaged values) transport events during 4-6 January, 7 April-17 May, and 24-29 September, with values as low as about 20 Sv, and an unusually high transport 10-31 December, with values as high as about 42 Sv. Because these events were relatively short lived, it is likely they are local responses to upstream atmospheric forcing and coastally trapped wave processes and are not particularly indicative of a climatically important shift (e.g., Mooers et al 2005). Interannual fluctuations in the Florida Current show a negative correlation (r ~ 0.6) with the NAO during the 1982-98 time period (Baringer and Larsen 2001); however, while the NAO has been tending to decrease over the past 20 years, the Florida Current transport shows no corresponding long-term trend through (Meinen et al 2009, manuscript submitted to J. Geophys.…”
Section: ) Long-term Changes In Surface Currentsmentioning
confidence: 99%